2016
DOI: 10.1109/tip.2016.2576399
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Quality of Videos Displayed With Local Dimming Backlight at Different Peak White and Ambient Light Levels

Abstract: This paper investigates the impact of ambient light and peak white (maximum brightness of a display) on the perceived quality of videos displayed using local backlight dimming. Two subjective tests providing quality evaluations are presented and analyzed. The analyses of variance show significant interactions of the factors peak white and ambient light with the perceived quality. Therefore, we proceed to predict the subjective quality grades with objective measures. The rendering of the frames on liquid crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Besides PSNR, Burini et al [26] also used Mean Square Error (MSE) and labPSNR which comes from PSNR to assess the impact of colour distortion of LCD images. To determine which characteristics of local backlight displays influence quality assessment, Mantel et al [27] conducted subjective and objective evaluations to investigate which aspects, such as clipping and leakage, are relevant for perceptual quality. Mantel et al [28] extended their work to investigate the impact of ambient light and peak white levels on the perceived quality of videos displayed using BLD methods.…”
Section: B Bld Algorithms Evaluationmentioning
confidence: 99%
“…Besides PSNR, Burini et al [26] also used Mean Square Error (MSE) and labPSNR which comes from PSNR to assess the impact of colour distortion of LCD images. To determine which characteristics of local backlight displays influence quality assessment, Mantel et al [27] conducted subjective and objective evaluations to investigate which aspects, such as clipping and leakage, are relevant for perceptual quality. Mantel et al [28] extended their work to investigate the impact of ambient light and peak white levels on the perceived quality of videos displayed using BLD methods.…”
Section: B Bld Algorithms Evaluationmentioning
confidence: 99%
“…The characteristic of vision is non-linear, it being too bright or too dark will cause varying degrees of damage to the quality of the image. As the bottom feature of image, brightness feature will directly affect the result of image quality evaluation (Mantel et al, 2016 ). The basic information of the image or pixel can be obtained from the brightness characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…80 ML methods, primarily neural networks, have also been tested to control the local backlight dimming, which is important for less loss of image detail, higher contrast ratio, and low power consumption of LCDs. [81][82][83] A comparative study of local backlight dimming prediction accuracy applied to the subjective evaluation of video quality, impacted by ambient light exposure and peak white (maximum display brightness), revealed that Elastic Net algorithm performed best compared to partial least squares regression and support vector regression. 81 The CNN-based algorithm made it possible to control the backlight intensity along with reducing the loss of detail while achieving a high contrast ratio by taking into account the diffusion property of light and leakage property of liquid crystal.…”
Section: Quality Assessment Of Liquid Crystal Displaysmentioning
confidence: 99%
“…[81][82][83] A comparative study of local backlight dimming prediction accuracy applied to the subjective evaluation of video quality, impacted by ambient light exposure and peak white (maximum display brightness), revealed that Elastic Net algorithm performed best compared to partial least squares regression and support vector regression. 81 The CNN-based algorithm made it possible to control the backlight intensity along with reducing the loss of detail while achieving a high contrast ratio by taking into account the diffusion property of light and leakage property of liquid crystal. 82 However, this ML method required statistical information of pixel values in each local block.…”
Section: Quality Assessment Of Liquid Crystal Displaysmentioning
confidence: 99%